2021
DOI: 10.1002/adfm.202100805
|View full text |Cite
|
Sign up to set email alerts
|

Rebirth of Aspirin Synthesis By‐Product: Prickly Poly(salicylic acid) Nanoparticles as Self‐Anticancer Drug Carrier

Abstract: As a great drug, aspirin has been used to treat many important diseases. To expand the biomedical applications of the aspirin material family, in this report, the authors polymerized salicylic acid (functional part of aspirin) into poly (salicylic acid) (PSA), which was once a by‐product during aspirin synthesis. PSA can be formulated into sub‐100 nm prickly nanoparticles (NPs) via a nanoprecipitation self‐assembly procedure. The PSA NPs are found to be nontoxic to normal cells and cancer cells, but can inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 34 publications
0
35
0
Order By: Relevance
“…Herein, the small size brain-targeting SPP-ARV-825 drug micelle was developed for glioma therapy. Nanoplatform delivery system has been widely used for drug delivery due to its advantages of good bioavailability, sustained drug release and reduced side effects 62 , 63 , 64 . As a promising anti-tumor drug candidate, the low water solubility of ARV-825 limits its application in cancer therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Herein, the small size brain-targeting SPP-ARV-825 drug micelle was developed for glioma therapy. Nanoplatform delivery system has been widely used for drug delivery due to its advantages of good bioavailability, sustained drug release and reduced side effects 62 , 63 , 64 . As a promising anti-tumor drug candidate, the low water solubility of ARV-825 limits its application in cancer therapy.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that biodegradable polymers such as poly (ursolic acid) are used as drug carriers for treating CRC and other cancers. The anticancer drug effectively loaded into poly(salicylic acid) nanoparticles shows ultrahigh blood vessel penetration, tumor penetration, and tumor accumulation due to the special prickly nanostructure (107,108). Thus, the combination of a therapeutic polymer platform and immunotherapy to achieve precise targeted therapy may be a new attractive therapeutic strategy for treating digestive tract cancer.…”
Section: Perspectivementioning
confidence: 99%
“…Clinically, surgical resection has been the most widely applied treatment for melanoma but suffered from the high risk of recurrence [ 5 ]. Other alternative therapeutic strategies have been investigated to eradicate the melanoma cells, including the chemo/radiotherapy and photodynamic therapy (PDT) [ 6 ]. Unfortunately, melanoma is resistant to the traditional chemo/radiotherapy which could bring about endless pain to patients [ 7 ].…”
Section: Introductionmentioning
confidence: 99%